PERLINDUNGAN KONSUMEN PENYANDANG DISABILITAS TERHADAP AKSES PELAYANAN PUBLIK TRANSPORTASI UMUM TRANSJAKARTA: Protection Of Consumers With Disabilities Towards Access To Public Transportation Services Transjakarta - Grace Michaela Japranata; Anna Maria Tri Anggraini (AMICUS CURIAE, 2025)
Indonesian people often rely on public transportation, including people with disabilities, who frequently encounter obstacles in accessing Transjakarta bus transportation.  Several Transjakarta bus stops have no ramps, wheelchair lanes, or guide lanes. The Identification problem is analyzes the suitability of public service accessibility facilities, as outlined in DKI PERDA and Law No. 8 of 2016, and their consequences. This research employed the Normative Law research method, which is descriptive and then the data were analyzed qualitatively to facilitate deductive conclusions. It is result and concluded that the accessibility of public services provided by Transjakarta is unable to regulations and policies. This is shown by the inadequate facilities available for people with disabilities and the legal consequences for Transjakarta that does not provide special facilities for passengers with disabilities can result in sanctions by applicable laws and regulations, most of the sanctions are in the form of administrative sanctions such as written warnings, administrative fines, license suspension, and license revocation, and provide compensation for losses experienced. The author suggests that Transjakarta pay attention to facilities, laws, regulations, and local governments to ensure the APBD budget for the development of accessibility services for passengers with disabilities.